Pengaruh Kombinasi Kompres Hangat dan Dzikir terhadap Tingkat Nyeri pada Pasien Gastritis - Syamdarniati; Indah Wasliah (Insan Kreasi Media, 2024)
Gastritis is an inflammation (inflammation) of the gastric mucosa caused by irritating and infectious factors, namely increased stomach acid. of the many factors that cause gastritis make the incidence of gastritis increase, due to irregular and unhealthy eating habits, alcoholic beverages, stress and consuming lots of coffee which can stimulate increased production of stomach acid. This community service activity was carried out by providing a combination therapy of warm compresses and dhikr therapy to reduce the pain sensitivity of patients with gastritis, with a total of 17 respondents. The aim of implementing this community service is to increase knowledge, reduce pain levels, empower patients and families, improve the quality of life of patients and to encourage the use of complementary therapies in health care and increase community participation in health programs. After the pre-test and post-test, it can be concluded that the combination of warm compresses and dhikr can reduce pain levels in gastritis patients. So it is recommended for gastritis sufferers to do warm compresses and dhikr as an alternative therapy when feeling pain.